2015
DOI: 10.1002/hep.27664
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis C viral infection with incidence and progression of chronic kidney disease in a large cohort of US veterans

Abstract: Background An estimated 4 million Americans have been exposed to the hepatitis C virus (HCV) in the US population. The risk of incident and progressive chronic kidney disease and of mortality in patients with normal kidney function infected with HCV is unclear. Methods In a nationally representative cohort of 100,518 HCV+ and 920,531 HCV- US Veterans with normal baseline estimated glomerular filtration rate(eGFR), we examined the association of HCV infection with: (1)all-cause mortality, (2)incidence of decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
145
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(152 citation statements)
references
References 34 publications
6
145
1
Order By: Relevance
“…Data were obtained from the Racial and Cardiovascular Risk Anomalies in chronic kidney disease (CKD; RCAV) study, which examines risk factors of incident CKD, mortality, and other outcomes in US veterans, and which was previously described in detail [16,17].…”
Section: Study Setting and Cohort Definitionmentioning
confidence: 99%
“…Data were obtained from the Racial and Cardiovascular Risk Anomalies in chronic kidney disease (CKD; RCAV) study, which examines risk factors of incident CKD, mortality, and other outcomes in US veterans, and which was previously described in detail [16,17].…”
Section: Study Setting and Cohort Definitionmentioning
confidence: 99%
“…Most comorbid conditions and unadjusted outcome rates increased across groups from patients with no evidence of renal disease to non-ESRD There is an established relationship between HCV and CKD. Patients with HCV are at risk of developing certain types of renal disease (e.g., mixed cryoglobulinemia with membranoproliferative glomerulonephritis) [11] and may be more likely to develop CKD [12] , and CKD may progress faster in patients with HCV than in those without HCV [13][14][15] . In ESRD patients on maintenance dialysis, the prevalence of HCV increases with dialysis duration [16] , potentially due to transmission from blood products or contaminated equipment [11] .…”
mentioning
confidence: 99%
“…10 Recent studies suggest that HCV-infected patients with CKD have an accelerated rate of kidney function loss and an increased risk of progressing to ESRD. [14][15][16][17][18][19] In one study, Molnar et al 19 showed that HCVinfected patients with CKD had an increased mortality and an accelerated rate of progression to ESRD, raising the important question of whether treating to obtain a sustained virologic response defined as an undetectable viral load 12 weeks after completion of treatment (SVR12) would diminish the rate of decline in GFR.…”
Section: Hcv In Patients With Kidney Diseasementioning
confidence: 99%